ECOTHEOLOGY OF WOMEN’S ENVIRONMENTAL ACTIVISM IN THE WADAS AGRARIAN CONFLICT - Iqtamar Muhammad; Siti Khuzaimah (Religi: Jurnal Studi Agama-agama, 2026)
This paper seeks to examine the discourse of eco-theology and women’s participation in efforts to resolve the agrarian conflict in Wadas Village. The agrarian conflict in Wadas Village originated from a government policy, namely the Bener Dam National Strategic Project, in which Wadas Village was designated as a strategic area for the extraction of andesite stone for the dam. The conflict has been ongoing for a long time and has involved many people, especially women. During the conflict, women’s presence and participation in responding to this policy took the form of a women’s movement consisting of young women and mothers in Wadas Village, namely Wadon Wadas. This movement was launched to voice the concerns of the women of Wadas village regarding government policy and the establishment of an open-pit andesite quarry in Wadas village, which is considered to disrupt the stability of women’s lives. This paper is a descriptive-analytical qualitative study with an approach based on religious studies, socio-political conflict, and ecofeminism. The theory used is Françoise d’Eaubonne’s ecofeminism theory, which includes conservative, modern, and cultural ecofeminism. There are three issues discussed in this paper. First, the discourse of eco-theology and women’s participation in agrarian conflicts in Wadas village was formed from resistance to government policies that destroy nature and the stability of the lives of the people of Wadas village. Second, women consider nature to be integral to women's lives and that nature is also a living creature created by God, just like humans and animals. Third, women’s efforts to preserve nature include creating women’s movements that are environmentally friendly, emphasizing equality among fellow human beings, and practicing and promoting religious teachings about the importance of protecting nature, which is considered part of faith. Keywords: Agrarian Conflict, Discourse, Eco-Theology, Wadas, Women’s Participation     Tulisan ini berupaya mengkaji diskursus ekoteologi dan partisipasi perempuan dalam upaya resolusi konflik agraria di Desa Wadas. Konflik agraria yang terjadi di Desa Wadas merupakan konflik yang mulanya berasal dari kebijakan pemerintah, yakni Proyek Strategis Nasional Bendungan Bener, di mana Desa Wadas dijadikan sebagai daerah yang strategis dalam pengambilan bahan material bendungan berupa batu andesit. Konflik tersebut telah berlangsung sejak lama dan telah melibatkan banyak pihak, terutama perempuan. Selama konflik berlangsung, keberadaan dan partisipasi perempuan untuk menyikapi kebijakan tersebut dilakukan dengan mengusung gerakan perempuan yang terdiri dari remaja perempuan dan para ibu di desa Wadas, yakni Wadon Wadas. Gerakan ini diusung untuk menyuarakan kekhawatiran para perempuan Desa Wadas terhadap kebijakan pemerintah dan pengadaan tambang terbuka batu andesit (quarry) di desa Wadas yang dianggap dapat mengganggu stabilitas hidup perempuan. Tulisan ini merupakan penelitian kualitatif yang bersifat deskriptif-analitis dengan pendekatan studi agama, konflik sosio-politik, dan ekofeminisme. Teori yang digunakan ialah teori ekofeminisme Françoise d’Eaubonne yang meliputi ekofeminisme konservatif, modern, dan kultural. Terdapat tiga hal yang dibahas dalam tulisan ini. Pertama, diskursus ekoteologi dan partisipasi perempuan dalam konflik agraria di desa Wadas terbentuk dari adanya perlawanan terhadap kebijakan pemerintah yang merusak alam dan stabilitas hidup masyarakat Desa Wadas. Kedua, perempuan menganggap bahwa alam merupakan suatu kesatuan bagi kehidupan perempuan dan alam juga merupakan makhluk hidup ciptaan Tuhan, layaknya manusia dan hewan. Ketiga, langkah perempuan dalam upaya kelestarian alam ialah dengan membuat gerakan perempuan yang ramah terhadap lingkungan, mementingkan kesetaraan terhadap sesama manusia, serta mengamalkan dan menyuarakan ajaran agama tentang pentingnya menjaga alam yang dianggap sebagian dari iman. Kata Kunci: Diskursus, Ekoteologi, Konflik Agraria, Partisipasi Perempuan, Wadas